Veiling Religion: The Public Face of Czech Re-Entry Faith-Based Organizations - Beláňová, Andrea (International journal of offender therapy and comparative criminology, 2024)
Due to the lack of sufficient non-governmental prisoner re-entry services in the Czech Republic, many post-release activities are provided by faith-based organizations (FBOs). However, the Czech Republic is considered to be one of the most atheistic countries in the world. Most of the Czech population is at least apathetic toward organized religion. This study examines how re-entry FBOs present Christianity to the public in the religiously indifferent Czech Republic. The primary focus is on how the organizations present themselves to the public. We employ qualitative content analysis examining names, logos, mission statements, and other documents of 14 re-entry FBOs. The analysis reveals four general themes within the organizations’ public presentations: Ambiguity when expressing religious topics, Christianity as an offer, Christianity as a form of social movement (self-legitimization), and Christianity as a pro-social lifestyle.